If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9p + 7 = 6p + 5 Reorder the terms: 7 + 9p = 6p + 5 Reorder the terms: 7 + 9p = 5 + 6p Solving 7 + 9p = 5 + 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. 7 + 9p + -6p = 5 + 6p + -6p Combine like terms: 9p + -6p = 3p 7 + 3p = 5 + 6p + -6p Combine like terms: 6p + -6p = 0 7 + 3p = 5 + 0 7 + 3p = 5 Add '-7' to each side of the equation. 7 + -7 + 3p = 5 + -7 Combine like terms: 7 + -7 = 0 0 + 3p = 5 + -7 3p = 5 + -7 Combine like terms: 5 + -7 = -2 3p = -2 Divide each side by '3'. p = -0.6666666667 Simplifying p = -0.6666666667
| f(3)=3x^2-4x+5 | | 3ln(x+3)=-6 | | 2n-12=3n+9 | | (x+69)+2x=180 | | 10=5m(m-5) | | 8w+12=180 | | x^2-(-5)x+c=0 | | -122=2x-7(-3x-22) | | -15.00+0.39x=14.95+0.13 | | f(-2)=3x^2-4x+5 | | x^2-2x+y^2-6y-27=0 | | 9-5y=14 | | 9-5y=12 | | -6(5-2x)=-8 | | 9q^2-71q-36=0 | | 2(x^2)=2r^2 | | (0.3)(0.07)=x | | 5(x+x)=720 | | 6x^3+3x^2+12=0 | | f(2)=3x^2-4x+5 | | (7x+26)-(2x-4)=50 | | 3x+12x+8=16x | | 4-y=-x | | 5x+x=720 | | 4y-2=7y+4 | | (0.3)(0.07)= | | x=-2x-7 | | z/5-6=31/4 | | 4c+72=180 | | z^3-2iZ^2+z-2i=0 | | 2u^2-u+2=0 | | 17p+74+72=180 |